Higher education and its role in sustaining growth: the case of Algeria - Abirat Lakhdar; Halmous Lamine (Dirassat Journal Economic Issue, 2021)
Since independence, considerable efforts have been devoted by Algeria to the educational system reform, in all its stages. These reforms have resulted in huge financial expenditures, but the targeted educational policies, which have significant financial allocations, gave priority to quantitative expansion rather than quality and the promotion of creativity and research among students and researchers, especially as investment in the human element has become clear and real investment. Education has a priority now to ensure the competitiveness of the national economy and its macro- and sectoral balances, as well as ensuring the sustainability of economic growth and the realization of other sustainable advantages ... These represent the most prominent findings of the present study regarding the analysis of the relationship between education and growth in the case of Algeria, as a developing country whose economy is affected by structural imbalances that depend on its effectiveness on the recovery of fuel prices